Optimization of ultraviolet irradiation on eggs of African catfish, Clarias gariepinus for androgenesis - Nursyaza Haziqah Jumahat (Terengganu: Universiti Malaysia Terengganu, 2013)
This study was about the Ultraviolet optimization based on four distances and five durations to induce androgenesis which produce all male larvae in African catfish, Clarias gariepinus. There are two main aspects that important to produce androgenetic larvae which is UV exposure to eggs and cold shock to restore diploidy.